2019
DOI: 10.1111/jphp.13170
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial hypertrophy is improved with berberine treatment via long non-coding RNA MIAT-mediated autophagy

Abstract: Objectives This study aimed to evaluate berberine (BBR) effects on myocardial hypertrophy (MH) and associated mechanisms. Methods BBR effects on MH were evaluated in rats with constriction of abdominal aorta (CAA). qRT-PCR assay was used to measure MH-related genes, long non-coding RNAs (lncRNAs) and autophagy-related genes expressions. Western blot was performed to detect autophagy markers expression. Filamentous actin and phalloidin expressions were detected using immunofluorescence assay. Key findings BBR s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 58 publications
0
19
0
Order By: Relevance
“…In addition, berberine 147 was found to increase autophagic gene expression by reducing lncRNA MIAT expression in vivo and inactivating AMPK/mTOR pathway in vitro. Eisenberg et al 148 showed that spermidine feeding could extend the lifespan of the mice and protect against overloaded cardiac hypertrophy in the murine model due to enhanced autophagy and mitophagy.…”
Section: Natural Products In Preventing Pathological Cardiac Hypertmentioning
confidence: 97%
“…In addition, berberine 147 was found to increase autophagic gene expression by reducing lncRNA MIAT expression in vivo and inactivating AMPK/mTOR pathway in vitro. Eisenberg et al 148 showed that spermidine feeding could extend the lifespan of the mice and protect against overloaded cardiac hypertrophy in the murine model due to enhanced autophagy and mitophagy.…”
Section: Natural Products In Preventing Pathological Cardiac Hypertmentioning
confidence: 97%
“…Zeng et al. demonstrated that cardiomyocyte autophagy was enhanced by berberine-induced MIAT knockdown, which further contributed to the improved cardiomyocyte contractility ( Zeng et al, 2019 ). Therefore, development of a small molecule which can specifically target MIAT could be our next aim.…”
Section: Discussionmentioning
confidence: 99%
“…Still, another group described their work on evaluating the effects of berberine, an effective natural supplement compound extracted from several plants, on CH in a rat model with constriction of abdominal aorta and H9C2 cells stimulated with AngII to induce cardiomyocyte hypertrophy [58]. They depicted that berberine significantly relives CH and cardiomyocyte enlargement and expression of hypertrophy marker proteins.…”
Section: Lncr-miat and Cardiac Hypertrophymentioning
confidence: 99%